Effects of adding 5–20 mol% ZrC plus 5 mol% Cu as a sintering aid on microstructure and mechanical properties of the TaC ceramics. Issue 14 (1st November 2016) - Liu, Limeng; Geng, Guihong; Hai, Wanxiu; Chen, Yuhong; Wu, Laner
Abstract: TaC ceramics were prepared by hot pressing at 1900 °C for 30 min under 30 MPa mechanical pressure. Effects of the addition of 20 mol% ZrC or 5–20 mol% ZrC plus 5 mol% Cu as sintering aids on densification, phase composition, microstructure and mechanical properties of the consolidated materials were investigated. The results showed the pure TaC had a relative density of 86%of the theoretical value. Densities >97% theoretical were reached in the materials when the sintering aids were used. ZrC and TaC reacted to form solid solutions. The grain average size decreased from 18 µm in the pure TaC to 6 µm at 20 mol% addition. Addition of 5 mol% Cu further refined the microstructures. The 20 mol% ZrC+5 mol% Cu and the 10 mol% ZrC+5 mol% Cu composition had good flexural strength of 608 MPa and fracture toughness of 5.4 MPa m 1/2, respectively.